Enhancing yield and stress resilience in toria (Brassica rapa L.) through salicylic acid application under moisture stress conditions - Binod Kalita; Bidisha Borah; Jyoti Rekha Hazarika; Anju Mala Deka; Hiranya Kr Deva Nath; Rudra Narayan Borkakati; Ranjana Chakrabarty; Pabitra Kumar Bordoloi (Journal of Oilseed Brassica, 2025)
Moisture stress is a significant constraint affecting the yield of toria (Brassica rapa var. toria) in rainfed and semi-arid regions. Salicylic acid (SA), a plant growth regulator, plays a crucial role in mitigating abiotic stress and enhancing plant resilience. This study investigates the impact of foliar application of salicylic acid on the physiological traits, growth parameters, and yield of toria under moisture stress conditions. Results indicate that SA application improves photosynthetic efficiency, water use efficiency, and antioxidant defense mechanisms, leading to increased seed yield and oil content compared to untreated controls. These findings suggest that salicylic acid could be an effective strategy for enhancing toria productivity in moisture-deficient environments.